Development and study of hydromechanical method for cleaning sewage collectors from contamination - Goncharenko, Dmitriy; Zabelin, Sergey; Aleinikova, Alevtyna; Anishchenko, Anna; Hudilin, Roman (Eastern-European Journal of Enterprise Technologies, 2018)
In connection with bad state of existing sewer headers, there is a great need for quick and high-quality cleaning for their further operation. To extend service life of distribution systems, new technologies for their repair and recovery are being developed which makes it possible to ensure their stable functioning and as a result, provision of continuous drinking water supply and sewer disposal to improve quality of life for population. From an economic point of view, extension of service life of distribution systems through development of alternative repair technologies is promising as it will ensure their sustainable operation in conditions of limited financing. The proposed bucket design for cleaning the sewer headers has made it possible to identify the best option when using one design in different conditions. A new design of the bucket was proposed which enables cleaning of the sewage headers either separately in a purely mechanical way or with additional use of the hydraulic method. Thanks to such combined method, it is possible to eliminate dirt which cannot be qualitatively done separately with each of the existing methods in various technical and economic conditions. Purposefulness of application of the proposed method for cleaning sewage headers using the bucket of new design providing a combined method of operation was presented and justified. Examples of application of the new method for cleaning the headers using the bucket of new design were given. The obtained indicators confirm quality of the sewage header cleaning when working in various conditions, both technical (diameter, length and type of the header material, degree, and nature of foulness) and economic (work duration, energy, and water costs). Thanks to the use of this method, 75...85 % dirt elimination in the sewage headers and pipelines have been achieved which confirms its effectiveness and possibility of reducing work duration as well as resource and energy saving in carrying out these works